Suitability of Work Roles and Organizational Commitment to Performance in Local Government Employees - Putu Budi Juniantari; Putu Indah Rahmawati; Ni Kadek Sinarwati (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose: Performance that is not optimal for employees is indicated by the amount of work carried out by employees that has not reached the target and does not meet the needs of society, employee engagement physically and psychologically at work is still relatively low, the suitability of employee work roles is not optimal, and commitment to the organization is still relatively low. All of this will affect the low level of performance of district government employees in achieving organizational goals. Design/methodology/approach: This study uses quantitative research with a causal research design. Data were analyzed using multiple linear regression analysis. Findings: This study found that work role suitability has a positive and significant effect on employee performance, organizational commitment has a positive and significant effect on employee performance, and there is a simultaneous significant effect between work role suitability and organizational commitment provided on employee performance. Paper type: Research paper